Ecologia da invasora Hedychium coronarium J. König (Zingiberaceae) - Castro, Wagner Antonio Chiba de (2014)
Because the importance of invasive plant species in biological diversity reduction and environmental quality depreciation, there is great studies need addressing these organisms development, invasive potential and changes in nutrient cycling at invaded areas. We evaluate the development, invasiveness and debris input of Hedychium coronarium, aggressive herbaceous weed of wetlands, as well as the invasiveness of riparian communities. The two-year population dynamics study found increased ramets mortality and births during the winter season, indicating primary effect strategy for ramets recruitment. The in situ and in vitro decomposition experiments demonstrated low mineralization rates comparing with others same habit and niche of macrophytes. Sinusoid and exponential models demonstrates stochasticity of development and debris accumulation of H. coronarim in invaded areas. Rhizomes showed histological responses to different soil moistures. In high moisture soils, we found great aerenchyma development. Under low moisture, rhizomes showed greater starch granules accumulation. Removal experiments presented alternations in the preferential vegetative or reproductive investments according to soil moisture and habits of competitors. We also noted the use of rhizomes as food resource by capybaras during the winter season.